Marketing Death: Culture and the Making of a Life Insurance Market in China - Lacbawan Jr., Macario B. (Kasarinlan: Philippine Journal of Third World Studies; Vol 29 No 1 (2014): The 2014 TWSC Writeshop)
Review of Marketing Death: Culture and the Making of a Life Insurance Market in China by Cheris Shun-ching Chan (Oxford, UK: Oxford University Press)